Spray dried durian powder - Siti Fatimah, Mohamad Ali (2010)
This study explains the process and the best parameteres to dry durian juice using laboratory scale spray dryer. The raw durian fruit bought is blended in the lab to squeeze out the juice before the process of spray dying. Calcium Carbonate is used as the anti-caking agent. In this process various ratio of durian to water and amount of maltodextrin is used and added to identify the best ratio of durian to water and amount of maltodextrin that should be added to make durian juice. Once the ratio of durian to water and amount of maltodextrin is determined, the variation in the temperature is done to find out the best temperature. For the part of analytical experiment, solubility analysis is done using the lab scale centrifugal machine. Solubility analysis is done on the best powder obtained. The final analysis done is the sensory evaluation. In this evaluation, students were randomly picked in the cafeteria. They were given the reconstituted juice and the produced powder to evaluate. The criteria being evaluated in this part are the appearance, flavor and the texture. The students were asked to rank all this categories following the scale of 1 to 5. From this evaluation the commercial value of produced durian powder can be studied. The powder is then stored in shelf for one month. From this research, it was found that durian juice can be powderised using the lab scale spray dryer. The suitable ratio of durian to water and amount of maltodextrin is 1:1 and 10% respectively and the best temperature is at 170°C. Durian powder has a solubility of 75.6% and that it has commercial values and can be marketed.